The Effect of Umrah Service Quality on Umrah Customer Satisfaction and Umrah Customer Loyalty: Evidence from Umrah traveling agents in Malaysia - Othman, Bestoon; Harun, Amran Bin (Technium Social Sciences Journal, 2021)
The main aim of this study is to explore the impact of the dimensions of Umrah service quality on customer satisfaction for Umrah and customer loyalty for Umrah in the travel industry. Increasingly intense competition and structural shifts in the business environment are now pushing companies to adopt a customer-focused strategy that elevates the value of customer-related constructs such as customer satisfaction, quality of service, and consumer loyalty in describing the success of a company. Umrah service efficiency, Umrah customer satisfaction, and Umrah customer loyalty were calculated from the literature using a 5-point Likert scale. Structural equation modeling was carried out to analyze the impact of Umrah service quality on customer satisfaction in Umrah and customer loyalty in Umrah. The result showed that all dimensions of service quality influenced customer satisfaction and loyalty of Umrah's customers. The study's key drawback is that it was confined only to the Malaysian nation. Second, the present study only focuses on the traveling industry in Umrah. The results clearly indicate the dimensions of the quality of Umrah service that the practitioners must concentrate on in order to provide a better quality of service.